2019
DOI: 10.1002/mar.21273
|View full text |Cite
|
Sign up to set email alerts
|

Negative brand meaning co‐creation in social media brand communities: A laddering approach using NVivo

Abstract: Social media brand communities (SMBCs) have been heralded for their co‐creative, participatory potential whereby consumers actively contribute to the proliferation of meaningful brand avenues in a virtuously circular relationship with brands. Elevated loyalty and enhanced brand equity have been posited repeatedly as likely outcomes of a positively engaged community of brand aficionados. However, evidence to the contrary as negative brand co‐creation or brand co‐destruction has been progressively piling up in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 60 publications
0
32
0
1
Order By: Relevance
“…While this indicates what marketing managers should do, exactly how these strategies should be implemented requires innovative approaches. One possible approach to engage the Gen Z maven is for brands to create and encourage participation in brand communities (Rossolatos, 2019). Habibi, Laroche, and Richard (2016) found that while supporting the brand community with strategies such as content or incentives is necessary, the role and strength of brand community leaders, like market mavens, is more important for building a brand community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this indicates what marketing managers should do, exactly how these strategies should be implemented requires innovative approaches. One possible approach to engage the Gen Z maven is for brands to create and encourage participation in brand communities (Rossolatos, 2019). Habibi, Laroche, and Richard (2016) found that while supporting the brand community with strategies such as content or incentives is necessary, the role and strength of brand community leaders, like market mavens, is more important for building a brand community.…”
Section: Discussionmentioning
confidence: 99%
“…While we have endeavored to identify the psychological antecedents and outcomes of market mavens in social media, future research can uncover the role of market mavens within brand communities (Rossolatos, 2019). Future research can also explore peer-to-peer social bonds between market mavens and brand community members (Kucharska, 2019).…”
Section: Future Research and Limitationsmentioning
confidence: 99%
“…The feelings identified in the topic related to the millennial generation can denote the importance that UGC communities bring to those. Therefore, based on these feelings, other research may focus on the specific analysis of expectations created by the UGC on negative or positive indicators shared through Twitter [63] as well as how users participate collaboratively [64].…”
Section: Discussionmentioning
confidence: 99%
“…AMs benefit the consumer‐brand relationship beyond easier access in unaided brand‐name recall situations (Fournier, 1998), but they are harder to create by marketers than SMs that gain from mere repetition (Schmidt & Eisend, 2015). One possibility to form brand‐related AMs can be the co‐creation of brand experiences by consumers in social media discourse (Herz & Brunk, 2017; Rossolatos, 2019), with a growing senior community posting episodes from their lives online (Pera et al, 2020). Further, autobiographical referencing in advertising can alter AMs (Braun et al, 2002) which could be a strategy, for example, in nostalgic advertisements targeting older consumers.…”
Section: Resultsmentioning
confidence: 99%